Euro area scenarios and their economic consequences for Slovenia and Serbia - Weyerstrass, Klaus (Managing global transitions, 2013)
Since 1999, divergences in international competitiveness led to an accumulation of current account deficits in the south and surpluses in the north of the euro area. With the aid of macro econometric models, this paper estimates the effects of an exit of Greece or of all GIIPS countries (Greece, Italy, Ireland, Portugal, Spain) on the economies of Slovenia and Serbia. An exit of one or more countries would affect other economies via the trade channel and credit constraints. Euro area members would additionally suffer from an increase of public debt due to non-performing loans of the European Stability Mechanism and devaluations of public bonds purchased by the European Central Bank. An exit of Greece alone would only marginally affect the economies of Slovenia and Serbia. An exit of all GIIPS countries or a euro area breakup would have dramatic negative consequences for output, unemployment and public finances.
Keywords: economy; gospodarstvo; sovereign default; ekonomska kriza; euro area break-up; evroobmočje; plačilna nesposobnost; razpad območja evra